Resting‐state brain connectivity after surgical and behavioral weight loss. (5th June 2015) - Lepping, Rebecca J.; Bruce, Amanda S.; Francisco, Alex; Yeh, Hung‐Wen; Martin, Laura E.; Powell, Joshua N.; Hancock, Laura; Patrician, Trisha M.; Breslin, Florence J.; Selim, Niazy; Donnelly, Joseph E.; Brooks, William M.; et al.
<x xml:space="preserve">Abstract</x> Objective Changes in food‐cue neural reactivity associated with behavioral and surgical weight loss interventions have been reported. Resting functional connectivity represents tonic neural activity that may contribute to weight loss success. This study explores whether intervention type is associated with differences in functional connectivity after weight loss. Methods Fifteen participants with obesity were recruited prior to adjustable gastric banding surgery. Thirteen demographically matched participants with obesity were selected from a separate behavioral diet intervention. Resting‐state functional magnetic resonance imaging was collected 3 months after surgery/behavioral intervention. ANOVA was used to examine post‐weight loss differences between the two groups in connectivity to seed regions previously identified as showing differential cue‐reactivity after weight loss. Results Following weight loss, behavioral dieters exhibited increased connectivity between left precuneus/superior parietal lobule (SPL) and bilateral insula pre‐ to postmeal and bariatric patients exhibited decreased connectivity between these regions pre‐ to postmeal (Pcorrected<0.05). Conclusions Behavioral dieters showed increased connectivity pre‐ to postmeal between a region associated with processing of self‐referent information (precuneus/SPL) and a region associated with interoception (insula) whereas bariatric patients showed decreased connectivity between these regions. This may reflect increased attention to hunger signals following surgical procedures and increased attention to satiety signals following behavioral diet interventions.